Government‐led innovation acceleration: Case studies of US federal government innovation and technology acceleration organizations. Issue 3 (10th March 2022) - Roberts, Patrick S.; Schmid, Jon
Abstract: How can agencies that have operational activities as a primary focus improve the procurement and transition of innovative technologies, particularly from the private sector? This study seeks to inform scholars and public‐sector managers about organizational design for innovation and technology acceleration using a systems approach. It examines three organizations responsible for mission‐oriented innovation: In‐Q‐Tel, stood by up the Central Intelligence Agency; the FBI's Operational Technology Unit; and the National Institute for Occupational Safety and Health (NIOSH). It finds that collaboration and mission‐inspiration can bridge public–private sector divides, but that distance from operators can slow technology adoption. It recommends establishing metrics for innovation investments and outcomes and gaining a better understanding of end user needs. Venture capital characteristics in quasi‐government innovation organizations show promise but are untested outside of defense and intelligence. This study contributes to the literature by analyzing technology acceleration rather than initiation, development, adoption, or diffusion. It also adds to the study of technology acceleration in mission‐oriented agencies that are less often the focus of R&D scholarship on big science. Resumen: ¿Cómo pueden las agencias que tienen actividades operativas como enfoque principal mejorar la adquisición y transición de tecnologías innovadoras, particularmente del sector privado? Este estudio busca informar a académicos y gerentes del sector público sobre el diseño organizacional para la innovación y la aceleración tecnológica utilizando un enfoque de sistemas. Examina tres organizaciones responsables de la innovación orientada a la misión: In‐Q‐Tel, apoyada por la Agencia Central de Inteligencia; la Unidad de Tecnología Operativa del FBI; y el Instituto Nacional de Seguridad y Salud Ocupacional (NIOSH). Encuentra que la colaboración y la inspiración de la misión pueden salvar las divisiones entre el sector público y el privado, pero que la distancia de los operadores puede retrasar la adopción de tecnología. Recomienda establecer métricas para inversiones y resultados en innovación y obtener una mejor comprensión de las necesidades del usuario final. Las características del capital de riesgo en las organizaciones de innovación cuasi gubernamentales son prometedoras, pero no se han probado fuera de la defensa y la inteligencia. Este estudio contribuye a la literatura al analizar la aceleración de la tecnología en lugar de la iniciación, el desarrollo, la adopción o la difusión. También se suma al estudio de la aceleración de la tecnología en agencias orientadas a la misión que, con menos frecuencia, son el foco de atención de los estudios de investigación y desarrollo en la gran ciencia. Abstract: 摘要 将业务活动作为重点的政府机构如何能提升创新技术采购和转型，尤其是来自私人部门的技术?本研究试图通过系统方法让学者和公共部门管理者了解用于创新和技术加速的组织设计。本研究分析了负责以任务为导向的创新机构:In‐Q‐Tel(为美国中央情报局提供服务)；美国联邦情报局的操作技术部门；以及美国国家职业安全卫生研究所(NIOSH)。本研究发现，协作和任务‐灵感能在公共部门和私人部门之间搭建桥梁，但经营者之间的距离能减缓技术采纳的速度。本研究建议，应建立创新投资和结果衡量标准，并更好地理解终端用户的需求。准政府创新组织中的风险投资特征看起来是有希望的，但还未在国防和情报范围之外经历检验。通过分析技术加速而不是技术创立、发展、采纳或扩散，本研究为相关文献作贡献。本研究还对以任务为导向的机构的技术加速研究作贡献，这类机构通常不是大科学研发文献的重点。